Speaking Skills Analysis of 4th Grade Students in Indonesian Language Object - Yayan Carliyan; Dina Nisa (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to describe the implementation of learning, analyze students' speaking skills, the factors that can influence them and the efforts to improve speaking skills in class VI MIN 1 Purwakarta. This research is motivated by the low participation of students in the Indonesian language learning process. The approach used in this study is a qualitative approach with descriptive methods and the type of data is qualitative data. The results of this study, it is known that the speaking skills of 4th grade students at the school are included in the low category with an average score of 59. Clearly, on the linguistic factor most of the students have been able to be skilled in speaking such as phoneme clarity and intonation accuracy, while on the linguistic factor non-linguistically most of the students have not been able to be skilled in speaking. The factors that affect the speaking skills of class VI students at the school are divided into two factors, namely internal factors that come from within the students such as concentration problems, fear of making mistakes, embarrassment to express, low motivation to learn, and external factors come from learning facilities, and the environment outside the school.Keywords: Elementary School, External Factors, Indonesian Language, Internal Factors, Speaking Skills.